Mindfulness and Emotional Intelligence as Predictors of Self-Efficacy in High School Students - Nie Lie; Heru Suherman; Budi Utomo (Jurnal Kependidikan)
This research aims to explore the potential of mindfulness and emotional intelligence as predictors of self-efficacy among high school students. A quantitative approach using a correlational design was employed, with 68 grade XI students at Bodhicitta Buddhist High School in Medan selected through purposive sampling. Data were collected using the Five Facet Mindfulness Questionnaire (FFMQ), Emotional Intelligence Scale, and General Self-Efficacy Scale (GSES). Multiple regression analysis revealed that emotional intelligence significantly influenced self-efficacy (p = 0.000), while mindfulness showed no significant effect (p = 0.067), although it exhibited a strong correlation (r = 0.659). The coefficient of determination (R² = 0.628) indicates that mindfulness and emotional intelligence collectively explain 62.8% of the variability in self-efficacy, while other factors account for 37.2%. The findings highlight that emotional intelligence is the dominant predictor of self-efficacy, whereas mindfulness is supportive. Given these results, emotional intelligence training is recommended as a key strategy for enhancing students' self-efficacy, while structured and long-term mindfulness interventions may further complement this development. The findings provide valuable insights for emphasizing the necessity of a holistic educational approach, blending emotional intelligence training with mindfulness-based strategies to enhance students' psychological resilience and academic success.